THE THEORY OF POSITIVISM AND THE JUDGES’ SOCIAL JURISPRUDENCE IN INDONESIA - Budiono, Arief; Pebriana, Lila Afrida; Rahayu, Sudi; Izziyana, Wafda Vivid (Varia Justicia, 2019)
Positivism is a branch of philosophy, which is a source of knowledge on positive law which is based on the Constitution applied. The positive law is made by the law-making institution. The laws which have been determined and issued must be complied with by all citizens. It is enforced and it comes with strict sanctions. Judges have a big role in enforcing the aims of the law, which are certainty and justice. Apart from holding on to the formal law (the positive law), the judges also have the capability to see the condition in the field empirically and adjust to it flexibly. Thus, judges may have more flexibility in deciding upon a case and in examining the real data to uphold justice. Such decisions may be followed by other judges, which is called jurisprudence